Contradictory stakeholder expectations for sustainability reporting - a social contract theory approach - Kristiina Joensuu; Marileena Mäkelä; Tiina Onkila (Edward Elgar Publishing, 2022)
Sustainability reporting has recently faced increasing criticism. In particular, the legitimacy and accountability of the reports have been questioned. Despite these questions, there has been little further study on how stakeholders’ expectations are influenced by assumptions of a social contract. In this study we examine stakeholders’ views on sustainability reporting by applying nano-level social contract theory. Our research question is: how do stakeholder interpretations differ concerning sustainability reporting when it comes to meeting the requirements of the social contract? We interviewed representatives of internal and external stakeholders of two Finnish companies on the usability and challenges of sustainability reporting. The study constructs a typology of stakeholder expectations and the social norms influencing these expectations. The study contributes to the current literature by showing how the stakeholder expectations are contradictory, not only between different stakeholder groups, but also among individuals within those groups.
Social Innovation and Sustainable Entrepreneuship